VISUALISASI BUNGA ANGGREK DALAM KARYA TAPESTRI - SHINTA MISWARI, Drs. Erwin A, M.Sn., Drs. Mediagus, M.Pd. (Serupa The Journal of Art Education, 2017)
The purpose of the creation of the final work is to visualize and express the admiration, interest, and aesthetic experience of the author on the beauty /aesthetics of orchids through tapestry techniques. The method of creating artworks uses five stages: preparation stage, elaboration stage, synthesis stage, concept realization stage, and completion stage and the last one is exhibition of tapestry. Tapestry works using techniques (Flat, Klim, Soumak, and Giordes) with embroidery techniques. In this work is a picture of anxiety writers against orchid flowers that have been on the verge of extinction. Behind the beauty of orchids has so many benefits in human life.Keywords: Orchid Flower, Tapestry, and Embroidery